PENGARUH PITA PENGGADUH MELINTANG TERHADAP KECEPATAN KENDARAAN RINGAN DAN ANGKA KECELAKAAN DI JALAN TOL CIPULARANG - Meydita, Nindya; Kusumawati, Aine (Jurnal Transportasi, 2012)
Safety is one of the main considerations in designing toll roads. Vehicle running at speed higher than the speed limit contribute to such a high number of traffic accident. PT Jasa Marga, the operator of Cipularang toll road, has taken preventive actions to reduce the number of accidents by installing transverse rumble strips. The objective of this study is to determine the effect of installing transverse rumble strips at Cipularang toll road in reducing the speed of light vehicles and the number of accidents. Using parametric and non-parametric tests, this study showed that the transverse rumble strips do not affect the speed of light vehicles. In addition, the transverse rumble strips has no significant effect in reducing the number of accidents either.Keywords: traffic safety, toll roads, transverse rumble strips, traffic accidents.